Keratoprosthesis, Dohlman Type I device for a patient with repeated corneal graft failure - Bajracharya, L; Gurung, R; Tabin, G (Nepalese Journal of Ophthalmology, 2012)
Background: Keratoprosthesis (Kpro) surgery is performed in patients in whom traditional penetrating keratoplasty (PK) surgery has no hope for graft survival. The burden of corneal blindness is high in a developing country like Nepal. Case: A thirty-year-old man, with multiple graft failure in his only eye, underwent Kpro surgery. He had ambulatory vision and a stable Kpro 29 months after the surgery. Conclusion: Kpro surgery has been introduced in the country with this as the first case. Patients with poor prognosis for PK can benefit from this type of surgery. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5869 NEPJOPH 2012; 4(1): 165-169